EFFECT OF STANDARD TANNIN ON IN VITRO RUMEN METHANE REDUCTION AND RUMEN FERMENTATION CHARACTERISTICS - A. Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Methane is normally emitted by ruminants and represents a loss of feed energy by 8-12 %. Various feeding strategies are used to reduce the methane emission from ruminants for sustainable animal production. In this context an experiment was conducted to find out the effect of a standard tannin on rumen methane reduction and rumen fermentation characteristics for dairy cattle by in vitro gas production technique (IVGPT). The IVGPT was carried out by incubating the Cumbu Nappier hybrid (CO4) grass and rumen liquor with standard tannin at varying level viz. 0, 1.03, 2.06, 3.09 and 4.12 % of substrate in six replicates in shaking water bath for a period of 24 hours. After 24 hours the total gas production and pH were measured and methane was estimated in Gas Chromatography. The in vitro true dry matter digestibility (IVTDMD) was estimated and methane emission (ml) per 100 mg truly digested substrate was calculated. The rumen fermentation characteristics were also studied. The total gas production was significantly (p<0.05) decreased in 2.06 %, 3.09 % and 4.12 % standard tannin supplemented groups than other treatment groups. The methane production was significantly (p<0.05) decreased by 11.98 %, 29.34 %, 33.47 % and 34.71 % in 1.03 %, 2.06 %, 3.09 % and 4.12 % tannin levels, respectively than control. A highly significant (p<0.01) reduction of methane was observed at minimum level of standard tannin (2.06 %) per 100 mg of truly digested substrate, when compared to control. The rumen ammonia nitrogen, total bacteria and total protozoa were significantly reduced in tannin treated groups when compared to control. The other fermentation characteristics viz. IVTDMD, pH, TVFA, acetic acid, propionic acid, butyric acid and acetate propionate ratio were not differed among treatment groups. It was concluded that at minimum concentration of 2.06 % of standard tannin significantly reduced the methane emission, percentage of methane on total gas production and methane (ml) per 100 mg of truly digested substrate (p<0.01) than control without any adverse effect on rumen fermentation characteristics by IVGPT.